Adaptation and instructional strategies of Indonesian pre-service teachers teaching non-English subjects in Thai classrooms - Ilyin, Masruratul; Ismiatun, Febti; Widowati, Diah Retno (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study explores how Indonesian pre-service teachers specializing in teaching non-English subjects adapt their instructional strategies in Thai classrooms, addressing challenges related to cultural and linguistic diversity. Using a qualitative case study design, data were collected through semi-structured interviews with two participants who taught mathematics and Indonesian language using English in Thai schools. The findings highlight the significance of cultural sensitivity, bilingual sources between Thai and English, and engaging instructional methods, such as visual aids, games, and songs, in overcoming communication barriers and fostering student engagement. Participants noted the critical role of simplifying language, reflective practices, and professional development in navigating cross-cultural teaching environments. Challenges included limited access to technology, language barriers, and managing classroom dynamics during transitional periods. The study underscores the need for language preparation and culturally responsive teaching strategies to ensure effective pedagogy in multicultural settings. While the small sample size limits generalizability, this research contributes valuable insights into the adaptation processes of pre-service teachers, advocating for enhanced training programs for international teaching practicums.